Enhancing microcirculation in STEMI patients: can intracoronary thrombolysis combined with thrombus aspiration provide an optimal strategy? - DongDong Yan; WenQiang Li; Ming Bai; Pei Wang; Zheng Zhang (Frontiers in Cardiovascular Medicine)
ST-elevation myocardial infarction (STEMI) is a critical cardiovascular emergency characterized by acute coronary artery occlusion and subsequent myocardial injury. The current standard of care is primary percutaneous coronary intervention (PPCI), which aims to rapidly restore epicardial blood flow. However, despite successful revascularization, microvascular obstruction (MVO) remains a major challenge, contributing to adverse clinical outcomes. This article explores the potential role of intracoronary thrombolysis, in conjunction with thrombus aspiration, in improving microcirculatory perfusion during PCI for STEMI patients. The pathophysiology of MVO is systematically reviewed, followed by an evaluation of clinical studies on thrombus aspiration and intracoronary thrombolysis in STEMI management. Furthermore, the potential benefits of combining these two approaches in mitigating MVO are discussed. Finally, the clinical evidence is critically assessed, existing controversies are analyzed, and directions for future research are proposed.